Spermatozoa from normozoospermic fertile and infertile individuals convey a distinct miRNA cargo. (27th September 2016) - Salas‐Huetos, A.; Blanco, J.; Vidal, F.; Grossmann, M.; Pons, M. C.; Garrido, N.; Anton, E.
Summary: Deciphering the underlying causes of idiopathic male infertility is one of the main challenges in reproductive medicine. This is especially relevant in infertile patients displaying normal seminal parameters and no urogenital or genetic abnormalities. In these cases, the search for additional sperm biomarkers is of high interest. This study was aimed to determine the implications of the sperm miRNA expression profiles in the reproductive capacity of normozoospermic infertile individuals. The expression level of 736 miRNAs was evaluated in spermatozoa from eight normozoospermic infertile males using TaqMan ® qRT‐PCR. Results were contrasted with data from 10 control normozoospermic fertile individuals analyzed under the same conditions. Clustering analysis of miRNA expression data separated the individuals according to their fertility condition (fertile and infertile). Fifty‐seven miRNAs were differentially expressed (DE‐miRNAs) between populations; 20 of them was regulated by a host gene promoter that in three cases comprised genes involved in fertility. The predicted targets of the DE‐miRNAs ( n  = 8, 606) unveiled a significant enrichment of biological processes related to embryonic morphogenesis and chromatin modification. Normozoospermic infertile individuals exhibit a specific sperm miRNA expression profile clearly differentiated from normozoospermic fertile individuals. This miRNA cargo has potential implications in the individuals' reproductive competence.